Exploring Pleiotropic Effects of Lipid Modifiers and Targets on Measures of the Coagulation System with Genetics - Schooling, C. Mary; Au Yeung, Shiu Lun; Zhao, Jie V. (Thrombosis and Haemostasis, 2022)
Background Statins have long been suspected to have pleiotropic effects via thrombotic factors. Randomized controlled trials are too limited to be definitive. We examined the associations of genetically mimicking effects of statins, PCSK9 inhibitors, and alternative lipid targets (in genes LDLR, APOC3, and LPL) on key indicators of coagulation system function, i.e., prothrombin time (PT) and activated partial thromboplastin time (aPTT).Methods We assessed the effect of established genetic mimics of effects of lipid modifiers and alternative lipid treatment targets on PT (n = 58,110) and aPTT (n = 37,767), all transformed to z-scores, using Mendelian randomization taking advantage of Biobank Japan. Ischemic heart disease (IHD) was a control outcome.Results Genetically mimicked effects of statins increased PT by 0.31 standard deviation (SD) per SD increase in low-density lipoprotein (95% confidence interval [CI]: 0.10–0.51) based on rs12916 but did not affect aPTT. Genetically mimicking effects of targeting LDLR increased PT based on rs688 (0.33 SD per SD increase in triglyceride, 95% CI: 0.03–0.63) but did not affect aPTT. Genetically mimicking effects of PCSK9 inhibitors or targeting APOC3 or LPL had no effect on PT or aPTT. Genetically mimicking effects of statins, PCSK9 inhibitors, and alternative lipid targets reduced risk of IHD in Biobank Japan.Conclusion Statins, and possibly targeting LDLR, may also act via a coagulation cascade factor, likely specific to the extrinsic or common pathway. Further elucidation of the mechanistic pathway may facilitate development of new interventions and inform use of statins particularly in relation to use of other anticoagulants.
Keywords: lipid modifiers; statins; Mendelian randomization; prothrombin time; activated partial thromboplastin time; platelets